ATMS - DECLINE OR DEVELOPMENT OF E-BANKING SERVICES - Jacek Binda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper is devoted to one of the channels of electronic banking – terminal banking. It presents the efforts of banking sector towards reducing the presence of cash in the financial turnover and lowering the costs of cash transactions thanks to development of high-tech ATM devices. The author points to the dynamics of changes related to the advances in this particular channel of contact, draws attention to the risks accompanying this form of contact and presents alternative forms of communication between a bank and its clients. The paper quotes data obtained from the Polish National Bank, the Polish Banks Association and EAST.